Loss of Ca(v)1.3 (CACNA1D) function in a human channelopathy with bradycardia and congenital deafness - Baig, Shahid M; Koschak, Alexandra; Lieb, Andreas; Gebhart, Mathias; Dafinger, Claudia; Nürnberg, Gudrun; Ali, Amjad; Ahmad, Ilyas; Sinnegger-Brauns, Martina J; Brandt, Niels; Engel, Jutta; Mangoni, Matteo E; et al. (Nature neuroscience, 2011)
Deafness is genetically very heterogeneous and forms part of several syndromes. So far, delayed rectifier potassium channels have been linked to human deafness associated with prolongation of the QT interval on electrocardiograms and ventricular arrhythmia in Jervell and Lange-Nielsen syndrome. Ca(v)1.3 voltage-gated L-type calcium channels (LTCCs) translate sound-induced depolarization into neurotransmitter release in auditory hair cells and control diastolic depolarization in the mouse sinoatrial node (SAN). Human deafness has not previously been linked to defects in LTCCs. We used positional cloning to identify a mutation in CACNA1D, which encodes the pore-forming α1 subunit of Ca(v)1.3 LTCCs, in two consanguineous families with deafness. All deaf subjects showed pronounced SAN dysfunction at rest. The insertion of a glycine residue in a highly conserved, alternatively spliced region near the channel pore resulted in nonconducting calcium channels that had abnormal voltage-dependent gating. We describe a human channelopathy (termed SANDD syndrome, sinoatrial node dysfunction and deafness) with a cardiac and auditory phenotype that closely resembles that of Cacna1d(-/-) mice.